MUHAMMAD IQBAL’S ISLAMIC EDUCATION PHILOSOPHY: CRITICAL ANALYSIS MBKM CURRICULUM - Khanafi, Ade Firman; Arifin, Syamsul; Mukhlis, Fahrudin (Sekolah Tinggi Agama Islam Sadra, 2025)
: Education and curriculum are a unity to support human life for the better, where the formulation of the curriculum must be based on physiological, sociological, and anthropological foundations to create good and perfect educational goals. Adjusting the curriculum to the times is a response so that education remains relevant and useful for human life. The Merdeka Learning Campus Merdeka (MBKM) curriculum is one of the answers to efforts to adapt to the times, where, in its implementation, the MBKM curriculum provides flexibility to educational institutions and students in the learning process to achieve the desired academic goals. In this study, the author will analyze the MBKM curriculum from the point of view of Islamic philosophy initiated by Muhammad Iqbal, namely Islamic educational reconstructionism and theistic existentialism. Although Muhammad Iqbal never wrote a specific work on education, his philosophical values can be used as a foundation in education because they contain a lot of meaning on how to make a complete human being in life. This research uses the library research method by collecting data from scientific journal articles related to the discussion of research and analyzing the data collected and interpreting it in a discussion. The result of this study is that the MBKM curriculum upholds the principles of independence and self-reliance, but in the view of Muhammad Iqbal’s reconstructionism and existentialism philosophy, there are shortcomings, namely the cultivation of intense spiritual values, individual and community relationships, and a sense of responsibility after freedom of choice. So that from Muhammad Iqbal’s point of view, which is based on creativity, freedom, and spirituality, the MBKM curriculum requires a review to create a holistic education to realize an insān kāmil person who is not only proficient in the field of worldly knowledge but also balanced with religious knowledge.